. Changes in serum cholyglycine and prealbumin levels, glutamyl transpetidase , and Alpha fetoprotein after Transcatheter Arterial Chemoembolization Combined with Microwave Ablation of Liver Cancer : serum cholyglycine and prealbumin levels, glutamyl transpetidase , and Alpha fetoprotein - Chen, Kang; Zhang, Chaojie; Sun, Feihu; Sun, Lei; Fan, Chen; Wang, Wei-Dong (Journal of Medical Biochemistry, 2025)
Introduction: It aimed to assess the clinical outcome of transcatheter arterial chemoembolization (TACE) and its combination with microwave ablation (MWA) in middle or advanced primary liver cancer(PLC), and to analyze the causes complications. Material and Method: According to the treatment methods, 100 patients with middle or advanced PLC were divided into TACE group (TACEG) and TACE+MWA group (combination group, CG) (50 cases in each). The TACEG was treated with TACE alone, and the CG adopted TACE combined with MWA. The quality of life (QoL)SF-36 score, serum liver function index, response, 1-year overall survival (OS) rate, and complication rate were observed before and following remedy. Result: As against the TACEG, following remedy, the CG had a higher SF-36 score,objective relief rate (ORR) (32% vs 50%), disease control rate (DCR)(82% vs 90%), and 1-year OS (60% vs 84%) and a lower 1-year complication rate (34% vs 16%);Following remedy, as against the TACEG, serum cholyglycine (CG) and prealbumin (PAB) levels were higher, and the levels of total bilirubin (TBil), direct bilirubin (DBil), alanine aminotransferase(ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), glutamyltranspetidase (GGT), and Alpha fetoprotein (AFP) were lower in the CG (all P<0.05). Conclusion: TACE combined with MWA is effective and safe in middle or advanced PLC, and can markedly improve liver function and postoperative survival rate(SR).